If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 19 = -96x Reorder the terms: 19 + 4x = -96x Solving 19 + 4x = -96x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '96x' to each side of the equation. 19 + 4x + 96x = -96x + 96x Combine like terms: 4x + 96x = 100x 19 + 100x = -96x + 96x Combine like terms: -96x + 96x = 0 19 + 100x = 0 Add '-19' to each side of the equation. 19 + -19 + 100x = 0 + -19 Combine like terms: 19 + -19 = 0 0 + 100x = 0 + -19 100x = 0 + -19 Combine like terms: 0 + -19 = -19 100x = -19 Divide each side by '100'. x = -0.19 Simplifying x = -0.19
| 5e-10+7=22 | | 7x-18=4x+18 | | -3+7=x-1 | | y=-9x+-4 | | X-1*4=3*4 | | 91+3p=583 | | 4+3=3+3 | | 7+5n=6n-1+1 | | (N-2)*180=165n | | -3(x+1)=-4x+14 | | 3x+7-5=25 | | 9x+x-8x= | | (N-2)*180=165 | | 9x+4y+8z-5x+5z-5y= | | 2x+38=153 | | mg=4 | | 8(h+67)=-32 | | .6666(x+4)=8 | | 12a-6a^2=-48 | | 12a-6a^2=48 | | 4x+8x+40=304 | | 2x-16=24x+27 | | (2w+3)(8+w)=0 | | -8(u-86)+15=-65 | | p=h+5 | | 19=3(n+2)+1 | | (2x-3)=(x+16) | | 15x-2x+3=10 | | 3p+8-7p= | | -7(5x+5)+4x=3x | | 7y-x=9 | | .024a-8=.224a+2 |